KONSEP NAFKAH MENURUT HUKUM PERKAWINAN ISLAM - Subaidi Subaidi (Isti`dal : Jurnal Studi Hukum Islam, 2014)
This article aims to show how to understand of living according to Islamic law, and what the implications of the maintenance towards family are. Through this library research, data processing is analyzed by descriptive analysis. The results of this study indicate that living can be understood as an obligation arising as a result of their deeds containing the burden of responsibility, that is payment of a fee in order to meet the needs of both primary and secondary to something that is under his responsibility. In addition, living in Islam also seen as a form of worship the implementation of which will have impacts not only materially- wordly, but also consideration of ascetic lifeKeywordsliving, contextual jurisprudence, family, Islamc law. Artikel ini bertujuan memaparkan bagaimana memaknai nafkah menurut hukum Islam, dan apa implikasi pemberian nafkah terhadap keluarga. Melalui penelitian kepustakan (library receach), pengolahan data dianalisa dengan analisis deskriptif. Hasil yang didapat dari studi ini menunjukkan bahwa nafkah dapat dirumuskan dalam pengertian kewajiban seseorang yang timbul sebagai akibat perbuatannya yang mengandung beban tanggung jawab, yaitu berupa pembayaran sejumlah biaya guna memenuhi kebutuhan baik primer maupun sekunder terhadap sesuatu yang berada dalam tanggungannya itu. Selain itu, nafkah dalam Islam juga dipandang sebagai bentuk ibadah di mana pelaksanaannya akan membawa akibat bukan hanya persoalan material-duniawi, tetapi juga pertimbangan kehidupan asketik.